An Unusual Case of Self-Inserted Rectal Foreign Body: Successful Management with Manual Extraction Under Spinal Anesthesia - Putut Tri Anda; Anton Tri Hartanto; Ade Tan Reza (HM Publisher, 2024)
Background: Rectal foreign bodies (RFBs) are an uncommon presentation to the emergency department (ED), often encountered by emergency medicine, surgery, and internal medicine specialists. Their management can be challenging, ranging from simple manual extraction to complex surgical interventions. Case presentation: A 19-year-old male presented to the ED with lower abdominal and anal pain. He admitted to self-inserting a plastic bottle into his rectum for autoerotic purposes. A physical examination revealed a palpable tubular mass in the rectosigmoid region, confirmed by a pelvic X-ray. The patient successfully underwent manual transanal extraction of the foreign body under spinal anesthesia, with no complications. Conclusion: This case highlights the importance of a thorough history and physical examination in patients presenting with RFBs. Prompt diagnosis and appropriate management, including manual extraction when feasible, can lead to successful outcomes.